PENGARUH METODE PEMBELAJARAN IOC (INSIDE OUTSIDE CIRCLE) TERHADAP KEAKTIFAN DAN PRESTASI BELAJAR SISWA (Studi Eksperimen Siswa Kelas X SMA NU Widasari pada Mata Pelajaran Ekonomi) - Lutfi Rohmawati (Equilibrium: Jurnal Penelitian Pendidikan dan Ekonomi, 2018)
Abstract: The purpose of this study was to find out: (1) An overview of student learning activeness between the experimental classes using the IOC learning method (Inside Outside Circle) and the control class using conventional learning methods. (2) Differences in the initial test (pre-test) of learning between the experimental classes using the IOC learning method (Inside Outside Circle) with the control class using conventional learning methods. (3) Differences in the final (post-test) learning tests between the experimental classes using the IOC learning method (Inside Outside Circle) and the control class using conventional learning methods. (4) Gain differences (pre-test and post-test) learning between the experimental classes using the IOC learning method (Inside Outside Circle) and the control class using conventional learning methods. The method used in this study is the Quasi Experiment method or Quasi Experiment. The research subjects were class X 9 students as a control class and class X 8 as an experimental class at 60 Ciawigebang Public High Schools. Data usage tools used are objective tests in the form of pre-test and post-test. Based on the results of statistical tests using the t test there was no difference in the initial test (pre-test) of learning between the experimental classes using the IOC learning method (Inside Outside Circle) with the control class using conventional learning methods; there is a difference in the final test (post-test) of learning between the experimental classes using the IOC learning method (Inside Outside Circle) and the control class that uses conventional learning methods; there are differences in Gain (pre-test and post-test) learning between the experimental classes using the IOC learning method (Inside Outside Circle) with the control class that uses conventional learning methods.Keywords: IOC Learning (Inside Outside Circle) Method, Activity, Student Learning Achievement.